Optimization of Public Participation Space in the State Budget Preparation Cycle - setiawan, lisno; masdi, Arief (Economic: Journal Economic and Business, 2022)
One of the arts in budgeting is finding a balance between ideal conditions and government decisions. Public participation is expected to be able to provide a solution to this dilemma. Public involvement in the preparation of the APBN in Indonesia is still relatively stagnant.. The constrain is that there is no mechanism for the public to channel feedback in the formulation of the Budget process. Therefore, this research is to identify a weak Indonesian OBI score and recommendation. By using qualitative methods, especially considering the institutions and business processes, the author formulates a mechanism in the framework of the Budget preparation cycle. The result of the study is that there are two mechanisms for public participation. The first mechanism is public participation in conjunction with the process of formulation of the APBN. It will fulfill the requirements of the OBI formalities, although it has limited time to accommodate follow-up actions. The second mechanism is public participation as a part of the performance budget and the policy evaluation process. It will start from the stipulation of the budget bill in the previous year until the beginning of the formulation of the Budget process. The benefit is the government easily accommodated the follow-up action in budget priorities. Both alternatives require regulatory improvements both in terms of business processes and institutions.